2018
DOI: 10.1111/jocn.14227
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of patients with non‐insulin‐treated type 2 diabetes on self‐monitoring of blood glucose: A qualitative study

Abstract: Healthcare professionals should reinforce patients' knowledge on appropriate responses to high and low blood glucose levels, intervene appropriately, discuss self-monitoring of blood glucose results with patients and track these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
2
10
0
1
Order By: Relevance
“…While insulin users were more likely to focus on using SMBG to adjust for the insulin doses, non-insulin users were more likely to focus on using SMBG to modify their lifestyles (habits and diets) which may be more variable based on daily activities. 3,6 The HbA1c benefits brought by increased SMBG observed in this study were in line with the SMBG targets recommended by international guidelines. According to the American Diabetes Association guideline, one additional SMBG test per day can reduce HbA1c level for 0.2% in patients with type 1 diabetes, and for patients with type 2 diabetes, SMBG is expected to reduce HbA1c by 0.25%-0.3% at 6 months.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…While insulin users were more likely to focus on using SMBG to adjust for the insulin doses, non-insulin users were more likely to focus on using SMBG to modify their lifestyles (habits and diets) which may be more variable based on daily activities. 3,6 The HbA1c benefits brought by increased SMBG observed in this study were in line with the SMBG targets recommended by international guidelines. According to the American Diabetes Association guideline, one additional SMBG test per day can reduce HbA1c level for 0.2% in patients with type 1 diabetes, and for patients with type 2 diabetes, SMBG is expected to reduce HbA1c by 0.25%-0.3% at 6 months.…”
Section: Discussionsupporting
confidence: 89%
“…One potential explanation for the inconsistence over 12 months is the different purposes of performing SMBG in insulin users and non‐users. While insulin users were more likely to focus on using SMBG to adjust for the insulin doses, non‐insulin users were more likely to focus on using SMBG to modify their lifestyles (habits and diets) which may be more variable based on daily activities …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sets of hypothetical self‐monitored blood glucose results were used to elicit descriptions of how the participants interpreted the values and the actions they would take if the values were their own. Chen, Hung, Chen, and Yeh (2018) found that some individuals use their blood glucose values to understand the relationship between their lifestyle and their blood glucose levels. Three sets of blood glucose data in both a line chart and table format were presented one at a time to the participant.…”
Section: Methodsmentioning
confidence: 99%